2012
DOI: 10.4236/ojped.2012.21001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of decision-making and patient participation in paediatric clinical trials: A literature review

Abstract: Background: Studies have shown that many drugs used in children may not have been authorised for use in this age group. This poses significant risks on children. A new EU regulation came into effect in 2007 to ensure that medicinal products that are researched, developed and authorised will also meet the therapeutic needs of children. This will mean an increased demand for children to participate in clinical trials. Objectives: To identify the needs and motivations of children and their families who have parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…In fact, suggestions from families to increase participation focused on educating individuals and emphasizing the importance of research for the benefit of all children. This finding is consistent with a recent review by Wulf et al (10) that reported personal benefit and altruistic motives as two essential reasons for participating in paediatric research. Perhaps this explains why incentives, a subject that remains controversial (18), were rarely emphasized by families to increase participation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, suggestions from families to increase participation focused on educating individuals and emphasizing the importance of research for the benefit of all children. This finding is consistent with a recent review by Wulf et al (10) that reported personal benefit and altruistic motives as two essential reasons for participating in paediatric research. Perhaps this explains why incentives, a subject that remains controversial (18), were rarely emphasized by families to increase participation.…”
Section: Discussionsupporting
confidence: 93%
“…Family engagement with paediatric research stems from the invitation and recruitment process: families must initially be invited to participate. However, many clinical studies fail because they are underpowered and unsuccessful in approaching and recruiting a sufficient number of participants, and while the inclusion of families' views regarding research is a relatively new subject in the literature (10), it may help in elucidating the decision-making process with regard to recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4, 810] Perceived harms included randomization, time demands, and general inconveniences. [10] Many parents have an insufficient understanding of the distinction between the child’s treatment options and options for clinical trial participation, as well as incomplete understanding of randomization [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Reasons for, or against, participation may be influenced by ethnic status, societal factors, and anxiety or stress, and concrete barriers such as time commitment, childcare, and transportation difficulties (9). Providing participants with inadequate information concerning the particulars of the research also interferes with the participants' ability to make well-considered decisions (10). Studies in adolescents, one of which concerned a hypothetical research project, demonstrated that several participants expected direct health benefit from being questioned and examined by the physician (11)(12)(13).…”
mentioning
confidence: 99%